2011
DOI: 10.1042/bst0390868
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial β-amyloid in Alzheimer's disease

Abstract: It is well established that the intracellular accumulation of Aβ (amyloid β-peptide) is associated with AD (Alzheimer's disease) and that this accumulation is toxic to neurons. The precise mechanism by which this toxicity occurs is not well understood; however, identifying the causes of this toxicity is an essential step towards developing treatments for AD. One intracellular location where the accumulation of Aβ can have a major effect is within mitochondria, where mitochondrial proteins have been identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…[22] In transgenic mouse models for AD and in human AD sufferers, 17-HSD10 has been shown to have increased expression levels and has gained considerable attention as a result of its ability to bind A, suppress A-induced apoptosis and free-radical generation in neurons. [11] It is known that the interaction between 17-HSD10 and A , A and A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) takes place in the nanomolar range (K d ~ 40-80 nM), [11] which agrees well with the low cellular concentrations of A peptide expected at the early stages of AD. In addition, mutagenesis and inhibition studies have suggested that the L D loop of 17-HSD10, comprising residues C91-D119, plays a critical role in A binding.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…[22] In transgenic mouse models for AD and in human AD sufferers, 17-HSD10 has been shown to have increased expression levels and has gained considerable attention as a result of its ability to bind A, suppress A-induced apoptosis and free-radical generation in neurons. [11] It is known that the interaction between 17-HSD10 and A , A and A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) takes place in the nanomolar range (K d ~ 40-80 nM), [11] which agrees well with the low cellular concentrations of A peptide expected at the early stages of AD. In addition, mutagenesis and inhibition studies have suggested that the L D loop of 17-HSD10, comprising residues C91-D119, plays a critical role in A binding.…”
Section: Introductionsupporting
confidence: 73%
“…However, a lack of -sheet structure at acidic pH cannot exclusively account for the observed lack of aggregation inhibition, as it has been shown that 17-HSD10 does not bind A (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), which is known to exhibit a -sheet conformation by CD and NMR studies. [63] In contrast, the conformation of the N-terminal region, residues 17-20 of A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) that constitute the binding interface with 17-HSD10, [11] is known to exhibit a random-coil/-helix/-sheet equilibrium that is highly dependent on pH conditions. [61,63,64] At pH 7-8, it has been demonstrated that residues 10-28, containing the putative 17-HSD10 binding interface, are in equilibrium between random coil and -helix conformations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the first group to propose mitochondrial functional defects as a mechanism for AD was primarily interested in oxidative stress as a mechanism (Blass and Gibson, 1991), it did not take long for researchers of A␤, by then dominating AD disease pathogenesis, to incorporate the mechanism of mitochondrial dysfunction into their reasoning (Kaneko et al, 1995). This view persists to the present day (Borger et al, 2011) and has remained largely unquestioned despite the implications of the prevalence of TNF in AD brains (section III) and the widely published capacity of this cytokine to induce both A␤PP and A␤ (section IV) and to directly cause mitochondrial dysfunction (see above). Young-Collier et al (2012) found that the reduced expression of mRNA of genes responsible for mitochondrial function in human AD neurons could not be duplicated with 3 days of culture with A␤ 1-42 (instead, expression rose); this might now encourage investigation into other possible mechanisms for the finding.…”
Section: Tumor Necrosis Factor and Mitochondrial Dysfunctionmentioning
confidence: 99%